The influence of transformational leadership style and organizational culture on employee performance through job satisfaction as an intervening variable - Fathorrahman, Fathorrahman; Salam, Nurdiana; Maryati, Maryati; Hidayat, Sholeh; Haerofiatna, Haerofiatna (Indonesia Auditing Research Journal, 2026)
This study looks at how organizational culture and transformational leadership style affect worker performance at PT Chandra Asri Pacific Tbk, using job satisfaction as an intervening variable. Purposive sampling was used to pick 81 employees for the study, which takes a quantitative approach utilizing a survey method. Multiple regression and path analysis approaches were used to examine the data, which were gathered using structured questionnaires. The findings show that corporate culture and transformational leadership significantly and favorably affect workers' job satisfaction. Additionally, employee performance is directly and significantly impacted by these factors. The association between organizational culture and performance was shown to be partially mediated by job satisfaction, which also had a substantial impact on employee performance. However, the association between transformative leadership and employee performance is not mediated by work happiness. These results imply that strong corporate cultures and effective leadership techniques are essential for improving worker performance, both directly and indirectly. The study highlights the importance of strengthening leadership quality, fostering a supportive organizational culture, and improving employee satisfaction to achieve sustainable organizational performance. The results provide practical implications for management in formulating human resource strategies aimed at improving productivity and organizational effectiveness in highly competitive industrial environments.